Changes in the anterior segment of the eye following uncomplicated pars plana vitrectomy. A review - Kopecky, Adam; Nemcansky, Jan (Biomedical papers, 2019)
Pars plana vitrectomy is currently the most common technique used in retinal surgery. Although primarily involving the posterior segment of the eye it also affects the anterior segment. As this is a less published topic, the aim of this paper was to review the literature on changes in the anterior segment after uncomplicated pars plana vitrectomy using data based literature search. The conclusions are that even in otherwise ophthalmologically healthy patients, complications may occur in the anterior segment. Surgeons need to pay utmost attention in glaucoma patients and in those with endothelial insufficiency who are at highest risk of complications. He/she must also correctly plan a potential cataract surgery if not already done earlier. From the literature, most of the changes in the anterior segment after uncomplicated PPV are found to be temporary.
Keywords: pars plana vitrectomy; anterior segment; corneal endothelium; ultrasound biomicroscopy; ophthalmology